Disposition of Mycophenolic Acid, Brevianamide A, Asperphenamate, and Ergosterol in Solid Cultures of Penicillium brevicompactum - Bird, B. A. (1982)
When Penicillium brevicompactum was grown between layers of dialysis membrane on Czapek-Dox agar for 3 days, no synthesis of mycophenolic acid, brevianamide A, asperphenamate, or ergosterol occurred. After removal of the uppermost membrane layer, aerial mycelium developed and all four metabolites were formed. The bulk of the mycophenolic acid that was formed was excreted into the medium, the bulk of the brevianamide A and asperphenamate was found in the aerial hyphae, and ergosterol was found in both vegetative and aerial mycelia.